Maximising the value of electricity storage - Staffell,IL; Rustomji,M (Journal of Energy Storage, 2016)
Grid-scale energy storage promises to reduce the cost of decarbonising electricity, but is not yeteconomically viable. Either costs must fall, or revenue must be extracted from more of the servicesthat storage provides the electricity system. To help understand the economic prospects forstorage, we review the sources of revenue available and the barriers faced in accessing them. Wethen demonstrate a simple algorithm that maximises the profit from storage providing arbitragewith reserve under both perfect and no foresight, which avoids complex linear programmingtechniques. This is made open source and freely available to help promote further research.We demonstrate that battery systems in the UK could triple their profits by participating in thereserve market rather than just providing arbitrage. With no foresight of future prices, 75-95% ofthe optimal profits are gained. In addition, we model a battery combined with a 322 MW wind farmto evaluate the benefits of shifting time of delivery. The revenues currently available are notsufficient to justify the current investment costs for battery technologies, and so further revenuestreams and cost reductions are required.